(untitled) (Лучшие интеллектуальные исследования, 2025)
Introduction. Uterine fibroids, also known as leiomyomas or myomas, are the most common benign tumours of the uterus, affecting up to 70-80% of women during their reproductive years. These growths are composed primarily of smooth muscle cells and varying amounts of fibrous connective tissue. Although benign and non-metastatic, fibroids can severely impact the quality of life, fertility, and reproductive outcomes in affected women. The burden of disease is especially significant among women of African descent, where fibroids tend to appear earlier, grow larger, and cause more severe symptoms.